A systematic literature review to identify evidence-based principles to improve online environmental education. Issue 5 (11th April 2022) - Merritt, Eileen G.; Stern, Marc J.; Powell, Robert B.; Frensley, B. Troy
Abstract: Many environmental educators shifted to online programs in the midst of the COVID-19 pandemic. We conducted a systematic literature review to identify program characteristics from digital environmental education experiences that are associated with one or more elements of environmental literacy. After reviewing 153 candidate articles, 32 articles that evaluated 47 diverse programs met our selection criteria. For each of these programs, we systematically coded the articles to identify guiding theories, program types, program characteristics, and outcomes assessed. We also identified the authors' explanations and empirical evidence for program characteristics that led to positive outcomes. In this paper, we synthesize the results and present 12 guiding principles that show promise in enhancing outcomes related to environmental literacy in online programs for K-12 students. These principles, which are defined and illustrated with examples from the literature, include: social-ecological connections, relevance, social interactions, role models, autonomy, active involvement, challenge, use of multiple modalities, positive framing, preparation, feedback and reflection.